The Effect of Elementary Education on the Relationship of Social Science to the Earth's Governance System - Mahmud Alpusari; Neni Hermita; Victor Amrifo; Tommy Tanu Wijaya (Universitas Muhammadiyah Purwokerto, 2020)
The sustainability of this research from Biermann has a focus on collaborating on the earth system governance network based on five research challenges namely architecture, agency, adaptability, allocation, and accountability. Research in order to link the relationship of social science with the earth's governance system. It turns out that the social system is very influential in the earth's governance system, so the need to instill the value of the value of love of nature since elementary education so that the impact of the social system on the earth's governance system in the future can be minimized. The results of this study indicate that social systems consisting of people, governments, and non-government actors must work together to deal with the impact of a dynamic earth governance system. For this reason, elementary education is needed to reduce the negative impact of changes in the earth's governance system through the cultivation of character education that loves the environment while having a sense of responsibility.